A Multi‐Scale Structural Engineering Strategy for High‐Performance MXene Hydrogel Supercapacitor Electrode. Issue 18 (2nd August 2021) - Huang, Xianwu; Huang, Jiahui; Yang, Dong; Wu, Peiyi
Abstract: MXenes as an emerging two‐dimensional (2D) material have attracted tremendous interest in electrochemical energy‐storage systems such as supercapacitors. Nevertheless, 2D MXene flakes intrinsically tend to lie flat on the substrate when self‐assembling as electrodes, leading to the highly tortuous ion pathways orthogonal to the current collector and hindering ion accessibility. Herein, a facile strategy toward multi‐scale structural engineering is proposed to fabricate high‐performance MXene hydrogel supercapacitor electrodes. By unidirectional freezing of the MXene slurry followed by a designed thawing process in the sulfuric acid electrolyte, the hydrogel electrode is endowed with a three‐dimensional (3D) open macrostructure impregnated with sufficient electrolyte and H + ‐intercalated microstructure, which provide abundant active sites for ion storage. Meanwhile, the ordered channels bring through‐electrode ion and electron transportation pathways that facilitate electrolyte infiltration and mass exchange between electrolyte and electrode. Furthermore, this strategy can also be extended to the fabrication of a 3D‐printed all‐MXene micro‐supercapacitor (MSC), delivering an ultrahigh areal capacitance of 2.0 F cm –2 at 1.2 mA cm –2 and retaining 1.2 F cm –2 at 60 mA cm –2 together with record‐high energy density (0.1 mWh cm –2 at 0.38 mW cm –2 ). Abstract : A strategy of multi‐scale structural engineering is proposed to fabricate high‐performance MXene hydrogel supercapacitor electrode with both vertically ordered macrostructure and the proton‐intercalated microstructure. This strategy also can be extended to the fabrication of 3D‐printed all‐MXene micro‐supercapacitor, delivering an ultrahigh areal capacitance together with record‐high energy density.